Intersectoral Migration in Southeast Asia : Evidence from Indonesia, Thailand, and the Philippines - Butzer, Rita; Mundlak, Yair; Larson, Donald F. (World Bank, Washington, DC, 2014)
Using time series data spanning three decades, the authors examine the determinants of sectoral migration in Indonesia, Thailand and the Philippines. They employ a principal components algorithm to address problems associated with trended and inter-correlated explanatory variables. Migration rates in the three countries are low relative to other developing countries with the consequence of persistent inter-sectoral income differentials. Even so, the rate of migration has been responsive to income ratios in each country. The migration rates were also affected by the absorbing capacity of non-agriculture, as indicated by several measures. In contrast to other studies, policy variables consisting of indicators of physical and human capital had little impact on the migration rate separate from that captured by relative incomes.